2021
DOI: 10.3389/fneur.2020.601628
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Properties of Dimethyl Fumarate Measured by Optical Coherence Tomography in Non-inflammatory Animal Models

Abstract: While great advances have been made in the immunomodulatory treatment of multiple sclerosis (MS), there is still an unmet need for drugs with neuroprotective potential. Dimethyl fumarate (DMF) has been suggested to exert both immunomodulatory and neuroprotective effects in MS. To investigate if DMF has neuroprotective effects independent of immunomodulation we evaluated its effects in the non-inflammatory animal models of light-induced photoreceptor loss and optic nerve crush. This might also reveal applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The anti-inflammatory capacity of DMFu showed beneficial effects in an autoimmune uveitis rat model ( Labsi et al, 2021 ) and optic neuritis murine model ( Zyla et al, 2019 ). Further, DMFu promotes the survival of retinal ganglion cells (RGCs) after optic nerve crush ( Mori et al, 2020 ) and protects against retinal degeneration in a light-induced photoreceptor loss mouse model ( Dietrich et al, 2020 ). Mechanistically, studies have shown that DMFu activates Nrf2/heme oxygenase-1 (HO-1) ( Zyla et al, 2019 ; Mori et al, 2020 ) and increases glutathione ( Nelson et al, 1999 ; Dietrich et al, 2020 ) to mediate its anti-inflammatory and anti-oxidative effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory capacity of DMFu showed beneficial effects in an autoimmune uveitis rat model ( Labsi et al, 2021 ) and optic neuritis murine model ( Zyla et al, 2019 ). Further, DMFu promotes the survival of retinal ganglion cells (RGCs) after optic nerve crush ( Mori et al, 2020 ) and protects against retinal degeneration in a light-induced photoreceptor loss mouse model ( Dietrich et al, 2020 ). Mechanistically, studies have shown that DMFu activates Nrf2/heme oxygenase-1 (HO-1) ( Zyla et al, 2019 ; Mori et al, 2020 ) and increases glutathione ( Nelson et al, 1999 ; Dietrich et al, 2020 ) to mediate its anti-inflammatory and anti-oxidative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Further, DMFu promotes the survival of retinal ganglion cells (RGCs) after optic nerve crush ( Mori et al, 2020 ) and protects against retinal degeneration in a light-induced photoreceptor loss mouse model ( Dietrich et al, 2020 ). Mechanistically, studies have shown that DMFu activates Nrf2/heme oxygenase-1 (HO-1) ( Zyla et al, 2019 ; Mori et al, 2020 ) and increases glutathione ( Nelson et al, 1999 ; Dietrich et al, 2020 ) to mediate its anti-inflammatory and anti-oxidative effects. Intriguingly, in this study, DMFu alone induces significant metabolic changes compared to DMSO-treated control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous in vitro studies on DMF effects in primary endothelial cells were carried out in human umbilical vascular endothelial cells (HUVEC) [ 24 ] and human brain microvascular endothelial cells (HBMVEC) [ 61 ]. By far, the potential role of DMF and its derivatives as protective agents for retinal diseases has received little attention [ 62 , 63 ]; our findings give a new impulse to this perspective and go further, suggesting that DMF can be repurposed in eye pathologies involving alterations of the endothelium and, more extensively, in ocular diseases characterized by oxidative stress and inflammation.…”
Section: Discussionmentioning
confidence: 74%
“…A detailed protocol can be found in the Supplementary Material . In brief, the eyes were dissected from 6 representative animals per group 12 weeks after immunization and processed as previously described ( 35 ). After paraffin embedding, eyes were longitudinally sectioned at 5 µm and stained with Iba1 (1:500, Wako chemicals) and Cy5 anti-rabbit (1:500, Millipore) as secondary antibody.…”
Section: Methodsmentioning
confidence: 99%